Utility of Photochemical Traits as Diagnostics of Thermal Tolerance amongst Great Barrier Reef Corals - Nitschke, Matthew R.; Gardner, Stephanie G.; Goyen, Samantha; Fujise, Lisa; Camp, Emma F.; Ralph, Peter J.; Suggett, David J. (Frontiers in Marine Science, 2018)
Light availability is considered a key factor regulating the thermal sensitivity of reef building corals, where excessive excitation of photosystem II (PSII) further exacerbates pressure on photochemical pathways already compromised by heat stress. Coral symbionts acclimate to changes in light availability (photoacclimation) by continually fine-tuning the photochemical operating efficiency of PSII. However, how this process adjusts throughout the warmest months in naturally heat-tolerant or sensitive species is unknown, and whether this influences the capacity to tolerate transient heat stress is untested. We therefore examined the PSII photophysiology of 10 coral species (with known thermal tolerances) from shallow reef environments at Heron Island (Great Barrier Reef, Australia), in spring (October-November, 2015) versus summer (February-March, 2016). Corals were maintained in flow-through aquaria and rapid light curve (RLC) protocols using pulse amplitude modulated (PAM) fluorometry captured changes in the PSII photoacclimation strategy, characterised as the minimum saturating irradiance (Ek), and the extent of photochemical ([1 – C], operating efficiency) versus non-photochemical ([1 – Q]) energy dissipation. Values of Ek across species were >2-fold higher in all coral species in spring, consistent with a climate of higher overall light exposure (i.e. higher PAR from lower cloud cover, rainfall and wind speed) compared with summer. Summer decreases in Ek were combined with a shift towards preferential photochemical quenching in all species. All coral species were subsequently subjected to thermal stress assays. An equivalent temperature-ramping profile of 1°C increase per day and then maintenance at 32°C was applied in each season. Despite the significant seasonal photoacclimation, the species hierarchy of thermal tolerance (maximum quantum yields of PSII (Fv/Fm), monitored at dawn and dusk) did not shift between seasons, except for P. damicornis (faster declines in summer) and Stylophora pistillata (total mortality in spring). Furthermore, the strategy for dealing with light energy (i.e. preferential photochemical versus non-photochemical quenching) was unchanged for thermally tolerant species across seasons, whereas thermally sensitive species switched between preferential [1 – Q] and [1 – C] from spring to summer. We discuss how such traits can potentially be used as diagnostic of thermal tolerance under non-stressed conditions.